Patterns of Acute Gastroenteritis (AGE) at Palhinandan Rural Municipality, Kushma, Nawalparasi, Lumbini Province: An Epidemiological Study - Vipul Das; Bishnu Dev Das (Asian Journal of Science, Technology, Engineering, and Art, 2026)
Acute gastroenteritis (AGE) remains a major public health concern in Nepal, particularly in rural settings where inadequate sanitation and hygiene continue to increase vulnerability to enteric disease. This study aimed to assess the incidence and distribution of AGE in Palhinandan Rural Municipality using secondary data from the Health Management Information System (HMIS 9.3). Employing a retrospective design, the study reviewed AGE cases recorded over a three-year period and analyzed their monthly, place-wise, and sex-wise distribution patterns. The findings indicate that AGE incidence remained relatively stable throughout the year but exhibited seasonal peaks in Chaitra and Baisakh. Spatial analysis further showed that Ward No. 3 consistently recorded the highest incidence across the three consecutive years, a pattern likely associated with population density and poor sanitation conditions. In terms of sex distribution, females were more frequently affected than males, possibly because of greater exposure to contaminated water and food during household activities. These findings demonstrate meaningful seasonal, spatial, and gender-based variations in AGE incidence within Palhinandan Rural Municipality. The study contributes context-specific evidence for local public health planning and underscores the need to strengthen water, sanitation, and hygiene practices, improve data management, expand health education and immunization, and promote early diagnosis and appropriate treatment. Targeted interventions in high-risk wards and among vulnerable groups are essential to reduce the burden of AGE in the community.